Developing an Accounting Application to Streamline Financial Statement Preparation for MSMEs - Nugraha, Leonardo Gilang Indra; Kartikasari, Dewi; Zega, Imanuel (E-Jurnal Akuntansi, 2024)
The primary objective of this research is to support MSME stakeholders in preparing financial reports using the MSME E-Account application. A quantitative descriptive approach was employed, incorporating observation and surveys as data collection methods. The MSME E-Account application has been designed in alignment with the SAK EMKM framework, ensuring compliance with established standards for micro, small, and medium enterprises. This application simplifies the process of financial reporting by enabling automatic data recording, which enhances the accuracy and efficiency of financial management. By reducing errors in recording and calculation, the application not only saves time but also facilitates business analysis, ultimately supporting business growth. It is particularly beneficial for MSME practitioners across various sectors, including those without a formal accounting education, as it offers a user-friendly, flexible, and accessible interface suitable for diverse industries. The research highlights the significant contribution of the MSME E-Account application in fostering the development and progression of MSME businesses. By streamlining workflows, the application ensures a more efficient data entry process, enabling users to manage financial records with minimal effort. Furthermore, comprehensive testing of the application confirms that all its features operate effectively, underscoring its reliability as a tool for financial management in the MSME sector.